OPTIMIZING THE MANAGEMENT OF SUSTAINABLE RIVER-BASED ECOTOURISM IN SUMEDANG REGENCY, WEST JAVA - Nafarisa Kamila, Nadia
The river ecosystem and its riparian are natural assets that have a strategic role in providing environmental services for life. Sustainable management is an absolute measure to ensure the quality of the river's ecological functions, one of which is the utilization of the area for tourism activities. The potential for river-based ecotourism in Sumedang Regency has a high appeal, especially in Citengah Village which is the upper reaches of the Cihonje River. However, this area is also vulnerable to landslides and flash floods which have caused economic, social, and environmental losses. In addition, low ecotourism competitiveness occurs due to a lack of collaboration between stakeholders in ecotourism management. Therefore, an optimization model is needed that integrates ecological, social, economic, and cultural aspects for sustainable management. This study aims to: (1) assess the suitability and carrying capacity of river-based ecotourism areas; (2) analyze the level of influence and interest of stakeholders who play a role in management of ecotourism; (3) determine the effectiveness of ecotourism competitiveness; and (4) creating a model for optimizing the management of sustainable river-based ecotourism. This research was conducted in five tourist objects located along the Cihonje River, namely Curug Gorobog, Nabawadatala, Sapatapaan, Kampung Karuhun, and Puteri River Inn. Assessment of ecological conditions was analyzed spatially, and field observations included an assessment of the suitability of ecotourism based on the quality of the vegetation, the level of disaster vulnerability, and the biophysical condition of the river. Carrying capacity is analyzed using the concept of carrying capacity of area for ecotourism. Assessment of socio-economic and cultural conditions is approached by analyzing the level of influence and interest of stakeholders, as well as analyzing the competitiveness of river-based ecotourism. Optimization modeling was made using the Powersim Studio 10 dynamic system. The results showed that the tourism suitability index value for Gorobog Waterfall was in the very suitable category (85%) with a carrying capacity of 245 people/day; Nabawadatala obtained the conditional category (58.75%) with a carrying capacity of 350 people/day; Sapatapaan, Kampung Karuhun, and Puteri River Inn fall into the appropriate category with respective values of 76.25% (237 people/day), 70% (737 people/day), and 65% (232 people/day). Stakeholders involved in river-based ecotourism management in. Sumedang Regency consists of ecotourism managers, Citengah Village Government, West Java Natural Resources Conservation Agency (BKSDA), Disparbudpora (department of tourism, culture, youth, and sport) Sumedang Regency, media companies, local communities, and tourists. The results of the mapping analysis show that the stakeholders involved have not fully played a role in accordance with their position as indicated by the pattern of low participation so that good coordination has not been built with one another. The competitiveness of ecotourism in Sumedang Regency is still weak, marked by an index of 2.95 out of a maximum value of 7. Based on the results of a multidimensional scale analysis, the most significant factors in determining the competitiveness of ecotourism in this region are purchasing power, lodging accommodations, and environmental sustainability. The optimization model for the sustainability of river-based ecotourism can increase the sustainability of ecotourism. This can be achieved by implementing the following management strategies: (1) rehabilitation of riparian areas; (2) optimizing the Destana program (Disaster Resilient Village); (3) controlling the number of visits according to the DDK; (4) packaging of travel packages; (5) training and mentoring for tourism workers; (6) increasing community involvement; (7) optimizing the partnership pattern between stakeholders; (8) increasing tourism promotion; (9) increase in government budget allocation; (10) improving the quality of infrastructure; and (11) increasing cultural preservation efforts. Implementing this strategy will increase ecotourism sustainability by 20% within 5 years.